Inculcation of basic concepts of integrated water resources management based on video animation - Setiawan, Dani Achmad Fiqri (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
The younger generation can be competent in contributing to maintaining the continuity and quality of water resources; therefore, it is prioritized that they have an understanding of the basic concepts of integrated water resources management. This service activity collaborates with the Al-Mabrur Mosque madrasah and the Baleendah Permai Complex community to carry out integrated water resources management (PSDAT) outreach activities. This activity aims to instill basic concepts of PSDAT knowledge in madrasah children so that they will be ready to contribute to implementing PSDAT in their surrounding environment. This PSDAT integrated water resources management outreach activity uses the outreach method. The outreach media used is audio-visual media in the form of animated videos. The participants in this PSDAT educational activity were Al-Mabrur Mosque madrasah children who were still in elementary school. Counseling participants began to understand the knowledge and examples of activities regarding integrated water resources management. Participants were very enthusiastic about implementing the knowledge they had gained in the Baleendah Complex environment.